CRIP1a inhibits endocytosis of G-protein coupled receptors activated by endocannabinoids and glutamate by a common molecular mechanism - Mascia, Fabrizio; Klotz, Lisa; Lerch, Judith; Ahmed, Mostafa H.; Zhang, Yan; Enz, Ralf (Journal of Neurochemistry, 2017)
The excitability of the central nervous system depends largely on the surface density of neurotransmitter receptors. The endocannabinoid receptor 1 (CB1 R) and the metabotropic glutamate receptor mGlu8 R are expressed pre-synaptically where they reduce glutamate release into the synaptic cleft. Recently, the CB1 R interacting protein cannabinoid receptor interacting protein 1a (CRIP1a) was identified and characterized to regulate CB1 R activity in neurons. However, underlying molecular mechanisms are largely unknown. Here, we identified a common mechanism used by CRIP1a to regulate the cell surface density of two different types of G-protein coupled receptors, CB1 R and mGlu8a R. Five amino acids within the CB1 R C-terminus were required and sufficient to reduce constitutive CB1 R endocytosis by about 72% in the presence of CRIP1a. Interestingly, a similar sequence is present in mGlu8a R and consistently, endocytosis of mGlu8a R depended on CRIP1a, as well. Docking analysis and molecular dynamics simulations identified a conserved serine in CB1 R (S468) and mGlu8a R (S894) that forms a hydrogen bond with the peptide backbone of CRIP1a at position R82. In contrast to mGlu8a R, the closely related mGlu8b R splice-variant carries a lysine (K894) at this position, and indeed, mGlu8b R endocytosis was not affected by CRIP1a. Chimeric constructs between CB1 R, mGlu8a R, and mGlu8b R underline the role of the identified five CRIP1a sensitive amino acids. In summary, we suggest that CRIP1a negatively regulates endocytosis of two different G-protein coupled receptor types, CB1 R and mGlu8a R.
EVALuna2:4771

Homodimerization of a proximal region within the C-terminus of the orphan G-protein coupled receptor GPR179 - Bachert, Wolfrat; Klotz, Lisa; Sticht, Heinrich; Enz, Ralf (Neurochemistry International, 2021)
G-protein coupled receptors exhibit numerous biological functions. The orphan G-protein coupled receptor GPR179 is a central component of a 1 Megadalton large signalling complex in the ON-pathway of the mammalian retina that assembles multiple proteins, including the metabotropic glutamate receptor mGluR6. Dimer formation is a hallmark of G-protein coupled receptors and some use intracellular C-termini for dimerization. Here we tested the dimerization properties of the intracellular C-terminal domains of mGluR6 and GPR179. While the C-termini of GPR179 and mGluR6 did not interact, we detected a robust homodimerization of a proximal region in the GPR179 C-terminus. Mapping studies defined a linear stretch of 64 amino acids as dimerization region. Bioinformatic analysis indicated that this dimerization region might adopt an α-helical structure that is predicted to dimerize by forming a coiled-coil. Based on these data, we speculate that homodimerization of GPR179 might contribute to the formation of large signalling complexes in the mammalian retina.
CRIS-Team Scopus Importer:2021-08-13
Keywords: C-terminus; Coiled-coil; GPR179; mGluR6; Protein-protein interaction; Retina

Localization of group II and III metabotropic glutamate receptors at pre- and postsynaptic sites of inner hair cell ribbon synapses - Klotz, Lisa; Wendler, Olaf; Frischknecht, Renato; Shigemoto, Ryuichi; Schulze, Holger; Enz, Ralf (The FASEB Journal, 2019)
Glutamate is the major excitatory neurotransmitter in the CNS binding to a variety of glutamate receptors. Metabotropic glutamate receptors (mGluR1 to mGluR8) can act excitatory or inhibitory, depending on associated signal cascades. Expression and localization of inhibitory acting mGluRs at inner hair cells (IHCs) in the cochlea are largely unknown. Here, we analyzed expression of mGluR2, mGluR3, mGluR4, mGluR6, mGluR7, and mGluR8 and investigated their localization with respect to the presynaptic ribbon of IHC synapses. We detected transcripts for mGluR2, mGluR3, and mGluR4 as well as for mGluR7a, mGluR7b, mGluR8a, and mGluR8b splice variants. Using receptor-specific antibodies in cochlear wholemounts, we found expression of mGluR2, mGluR4, and mGluR8b close to presynaptic ribbons. Super resolution and confocal microscopy in combination with 3-dimensional reconstructions indicated a postsynaptic localization of mGluR2 that overlaps with postsynaptic density protein 95 on dendrites of afferent type I spiral ganglion neurons. In contrast, mGluR4 and mGluR8b were expressed at the presynapse close to IHC ribbons. In summary, we localized in detail 3 mGluR types at IHC ribbon synapses, providing a fundament for new therapeutical strategies that could protect the cochlea against noxious stimuli and excitotoxicity.-Klotz, L., Wendler, O., Frischknecht, R., Shigemoto, R., Schulze, H., Enz, R. Localization of group II and III metabotropic glutamate receptors at pre- and postsynaptic sites of inner hair cell ribbon synapses.
CRIS-Team Scopus Importer:2019-12-17
Keywords: cochlea; IHC; mGlu receptor; mGluR

Metabotropic Glutamate Receptors at Ribbon Synapses in the Retina and Cochlea - Klotz-Weigand, Lisa; Enz, Ralf (Cells, 2022)
Our senses define our view of the world. They allow us to adapt to environmental stimuli and are essential for communication and social behaviour. For most humans, seeing and hearing are central senses for their daily life. Our eyes and ears respond to an extraordinary broad range of stimuli covering about 12 log units of light intensity or acoustic power, respectively. The cellular basis is represented by sensory cells (photoreceptors in the retina and inner hair cells in the cochlea) that convert sensory inputs into electrical signals. Photoreceptors and inner hair cells have devel-oped a specific pre-synaptic structure, termed synaptic ribbon, that is decorated with numerous vesicles filled with the excitatory neurotransmitter glutamate. At these ribbon synapses, glutama-tergic signal transduction is guided by distinct sets of metabotropic glutamate receptors (mGluRs). MGluRs belong to group II and III of the receptor classification can inhibit neuronal activity, thus protecting neurons from overstimulation and subsequent degeneration. Consequently, dysfunction of mGluRs is associated with vision and hearing disorders. In this review, we introduce the principle characteristics of ribbon synapses and describe group II and III mGluRs in these fascinating structures in the retina and cochlea.
CRIS-Team Scopus Importer:2022-04-08
Keywords: Bipolar cell; Cochlea; Dimerization; Inner hair cell; Metabotropic glutamate receptor; Photoreceptor; Protein interaction; Retina; Ribbon synapse; Short linear motif

MGluR7 is a presynaptic metabotropic glutamate receptor at ribbon synapses of inner hair cells - Klotz, Lisa; Enz, Ralf (The FASEB Journal, 2021)
Glutamate is the most pivotal excitatory neurotransmitter in the central nervous system. Metabotropic glutamate receptors (mGluRs) dimerize and can couple to inhibitory intracellular signal cascades, thereby protecting glutamatergic neurons from excessive excitation and cell death. MGluR7 is correlated with age-related hearing deficits and noise-induced hearing loss; however its exact localization in the cochlea is unknown. Here, we analyzed the expression and localization of mGluR7a and mGluR7b in mouse cochlear wholemounts in detail, using confocal microscopy and 3D reconstructions. We observed a presynaptic localization of mGluR7a at inner hair cells (IHCs), close to the synaptic ribbon. To detect mGluR7b, newly generated antibodies were characterized and showed co-localization with mGluR7a at IHC ribbon synapses. Compared to the number of synaptic ribbons, the numbers of mGluR7a and mGluR7b puncta were reduced at higher frequencies (48 to 64 kHz) and in older animals (6 and 12 months). Previously, we reported a presynaptic localization of mGluR4 and mGluR8b at this synapse type. This enables the possibility for the formation of homo- and/or heterodimeric receptors composed of mGluR4, mGluR7a, mGluR7b and mGluR8b at IHC ribbon synapses. These receptor complexes might represent new molecular targets suited for pharmacological concepts to protect the cochlea against noxious stimuli and excitotoxicity.
CRIS-Team Scopus Importer:2021-11-05
Keywords: cochlea; inner hair cell; metabotropic glutamate receptor; mGlu; ribbon synapse